Secreted novel AID/APOBEC-like deaminase 1 (SNAD1) – a new important player in fish immunology - Majewska, Anna M.; Dietrich, Mariola A.; Budzko, Lucyna; Adamek, Mikołaj; Figlerowicz, Marek; Ciereszko, Andrzej (Frontiers in Immunology, 2024)
The AID/APOBECs are a group of zinc-dependent cytidine deaminases that catalyse the deamination of bases in nucleic acids, resulting in a cytidine to uridine transition. Secreted novel AID/APOBEC-like deaminases (SNADs), characterized by the presence of a signal peptide are unique among all of intracellular classical AID/APOBECs, which are the central part of antibody diversity and antiviral defense. To date, there is no available knowledge on SNADs including protein characterization, biochemical characteristics and catalytic activity.We used various in silico approaches to define the phylogeny of SNADs, their common structural features, and their potential structural variations in fish species. Our analysis provides strong evidence of the universal presence of SNAD1 proteins/transcripts in fish, in which expression commences after hatching and is highest in anatomical organs linked to the immune system. Moreover, we searched published fish data and identified previously ,,uncharacterized proteins" and transcripts as SNAD1 sequences. Our review into immunological research suggests SNAD1 role in immune response to infection or immunization, and interactions with the intestinal microbiota. We also noted SNAD1 association with temperature acclimation, environmental pollution and sex-based expression differences, with females showing higher level. To validate in silico predictions we performed expression studies of several SNAD1 gene variants in carp, which revealed distinct patterns of responses under different conditions. Dual sensitivity to environmental and pathogenic stress highlights its importance in the fish and potentially enhancing thermotolerance and immune defense. Revealing the biological roles of SNADs represents an exciting new area of research related to the role of DNA and/or RNA editing in fish biology.